The Value of Posterior Cervical Angle as a Predictor of Vaginal Delivery: A Preliminary Study - Eun-Ju Kim; Ji-Man Heo; Ho-Yeon Kim; Ki-Hoon Ahn; Geum-Joon Cho; Soon-Cheol Hong; Min-Jeong Oh; Nak-Woo Lee; Hai-Joong Kim (Diagnostics, 2021)
Accurate prediction of failure to progress and rapid decision making regarding the mode of delivery can improve pregnancy outcomes. We examined the value of sonographic cervical markers in the prediction of successful vaginal delivery beyond 34 weeks of gestation. A retrospective chart review was carried out. Medical information of singleton gestations delivered at a single center from 1 July 2019 to 30 August 2020 was collected. Transvaginal sonographic records of cervical length, anterior and posterior cervical angles, and cervical dilatation were obtained and re-measured. The value of these markers and clinical characteristics of mother and baby on vaginal delivery were investigated and compared to women who underwent cesarean section. A total of 90 women met the inclusion criteria. The rate of vaginal delivery was 75.6%. There were no differences found in terms of maternal age, rate of abortion, induction of labor, premature rupture of membranes, preterm labor, hypertension, diabetes, cervical length, and neonatal sex and weight. The prediction of vaginal delivery was provided by parity, maternal body mass index, and posterior cervical angle. The area under the receiver operating characteristic curve for prediction of vaginal delivery was 0.667 (95% CI 0.581–0.864, p = 0.017) for the posterior cervical angle, with a cutoff of 96.5°. Regression analysis revealed a posterior cervical angle ≥96.5° in the prediction of vaginal delivery (adjusted odds ratio: 6.24; 95% confidence interval: 1.925–20.230, p = 0.002). Posterior cervical angle ≥96.5° is associated with successful vaginal delivery. It is simple and easy to measure and can be useful in determining the mode of delivery.